TRANSFORMASI DIGITAL MANAJEMEN PESANTREN : IMPLEMENTASI UQI SMART SYSTEM DI PONDOK PESANTREN MODERN UMMUL QURO AL-ISLAMI BOGOR - Dewi Septiani Dewi (As-Sulthan Journal of Education, 2026)
Digital transformation in the management of educational institutions has become an important necessity to improve the effectiveness of educational governance in the era of information technology development. This study aims to analyze the implementation of digital transformation in pesantren management through the application of the UQI Smart System at the Modern Islamic Boarding School Ummul Quro Al-Islami, Bogor. This research employed a qualitative approach using a case study method. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The results of the study indicate that the UQI Smart System is an integrated information system that functions as a centralized database in managing administrative and information services within the pesantren. This system facilitates administrators in managing various institutional data more systematically and increases efficiency in data management. In addition, the system provides easier access to information for parents or guardians of students to obtain updates related to their children's educational development in the pesantren, such as financial administration information, online report cards, and various educational activities. The implementation of this system also supports improved transparency of information services and strengthens communication between the pesantren and parents. Therefore, the implementation of the UQI Smart System represents an innovation in the digital transformation of pesantren management that can enhance the effectiveness of governance in Islamic educational institutions.